Hubungan Kebiasaan Minum Teh Terhadap Kejadian Gout Athritis Pada Warga Jamaah Masjid Al Manshuurin Yabansai, Waena Jayapura - Herlambang B Mulyono; Trajanus L Jembise (Jurnal Biologi Papua, 2018)
Tea is a common drink that consumed in Indonesia. Caffein is one of the ingredients of tea. coffee has been shown to increase urinary excretion which is also likely to increase uric acid excretion. Gout is a disease cause of high level of uric acid in blood stream.The aim of this study was to determine the tea drinkers influences serum uric acid level in the residents of Al Manshuurin Mosque Yabansai Waena Jayapura. We enrolled 45 participants in this cross sectional study. An assessment of various dietary intake amounts of substances such as tea was performed using a food frequency questionnaire. The content of tea (15 mg/cup) intake information from the past year. Descriptive and Chi square analysis were applied to identify any association of dietary intake with serum uric acid levels or the risk of gout arthritis. The results showed that the tea drinkers had a lower risk than the not tea drinkers (p= 0.01 respectively). The conclusion of this study is tea drinkers have lower uric acid levels in  blood.  Key words: Gout, Tea drinkers, uric acid